2017
DOI: 10.2105/ajph.2016.303564
|View full text |Cite
|
Sign up to set email alerts
|

Human Trafficking of Minors and Childhood Adversity in Florida

Abstract: Maltreated youths are more susceptible to exploitation in human trafficking. Sexual abuse in connection with high ACE scores may serve as a key predictor of exploitation in human trafficking for both boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 29 publications
5
82
0
Order By: Relevance
“…These factors are part of a larger spectrum of adverse childhood experiences, which are well documented to confer greater vulnerability to adverse outcomes including substance use and mental health problems 9,21 and in one study, shown to place youth at higher risk for commercial sexual exploitation 9 . Not surprisingly, the CSE youth in our sample demonstrated a high prevalence of both substance and mental health problems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These factors are part of a larger spectrum of adverse childhood experiences, which are well documented to confer greater vulnerability to adverse outcomes including substance use and mental health problems 9,21 and in one study, shown to place youth at higher risk for commercial sexual exploitation 9 . Not surprisingly, the CSE youth in our sample demonstrated a high prevalence of both substance and mental health problems.…”
Section: Discussionmentioning
confidence: 98%
“…Risk factors for both commercial sexual exploitation and mental health problems include high rates of childhood trauma exposure, homelessness, victimization related to sexual orientation, and violence and threats when trafficked. 9,10 Indeed, prevalence of mental health problems, including depression and PTSD, are especially high among this population 11 . A study of CSE youth from agencies and clinics in Northern California found that 30% of youth engaged in self-harming behaviors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research confirms that youth who have been sexually exploited have the highest numbers of ACES, with sexual abuse being the most common [8,9]. Poor family functioning or conflict is a significant contributing or exacerbating factor for running away or being asked to leave home [8][9][10].…”
Section: Microsystemmentioning
confidence: 98%
“…Adverse childhood experiences and ongoing adversity such as child abuse and neglect, homelessness (running away or being "thrown-away"), LGBTQ+ identity, and being involved with child welfare or criminal justice systems, all contribute to exposing youth to risky circumstances leading to their sexual exploitation [7]. Recent research confirms that youth who have been sexually exploited have the highest numbers of ACES, with sexual abuse being the most common [8,9]. Poor family functioning or conflict is a significant contributing or exacerbating factor for running away or being asked to leave home [8][9][10].…”
Section: Microsystemmentioning
confidence: 99%
“…Statistics from the United States Human Trafficking Reporting System indicate that 85% of identified sex trafficking victims were U.S. citizens/legal residents and 55% were minors . Risk factors associated with CST include a history of abuse, substance use, juvenile justice system involvement, a history of running away from home, and LGBTQ status …”
Section: Introductionmentioning
confidence: 99%